Introduction: “Medieval archival sources in the digital world. The challenge of treating and visualizing semi-structured data” - Rosselli Del Turco, Roberto; Salvatori, Enrica; Nanetti, Andrea; Giacchetto, Marco; Schwarz-Ricci, Vera Isabell; Ambrosio, Antonella (Umanistica Digitale, 2021)
The webinar <q>Medieval archival sources in the digital world. The challenge of treating and visualizing semi-structured data</q>, organized by the Laboratorio di Cultura Digitale and the head of the Engineering Historical Memory project, was held on 22-23 June 2020. This thematic dossier aims to offer a brief account of the results of the workshop held on a virtual platform, with particular attention to future collaboration and experimentation initiatives in the field of processing and extracting information from semi-structured editions of archival documents. Advanced functionalities of this type are in fact essential to broaden the use of digital editions of archival sources and other written documents, making them more flexible and open to algorithms’ reading tools. The central problem concerns the relationship between coding and the creation of interfaces that are as simple and immediate as possible, in which the user (human or artificial) can intuitively access.